Familial aggregation of gout and relative genetic and environmental contributions: a nationwide population study in Taiwan - Kuo, Chang-Fu; Grainge, Matthew J.; See, Lai-Chu; Yu, Kuang-Hui; Luo, Shue-Fen; Valdes, Ana M.; Zhang, Weiya; Doherty, Michael (BMJ Publishing Group, 2015)
OBJECTIVE: To examine familial aggregation of gout and to estimate the heritability and environmental contributions to gout susceptibility in the general population.